Download presentation

Presentation is loading. Please wait.

Published byKevin Battin Modified over 2 years ago

1
Algebraic Expressions and Identities

2
Identities to be remembered: (a + b) 2 = a 2 + b 2 +2ab (a - b) 2 = a 2 + b 2 - 2ab (x + a)(x + b) = x 2 + (a + b)x + ab (a - b)(a + b) = a 2 – b 2 (a+b) 3 = a 3 +b 3 + 3ab(a+b) =a 3 + 3a 2 b+3ab 2 + b 3 (a-b) 3 = a 3 - b 3 - 3ab(a - b) =a 3 - 3a 2 b +3ab 2 - b 3

3
The value of : (67.542) 2 - (32.458) a) 1 b)10 c)100 d)20 Choose the correct option:

4
Find the missing term in the following equation: (2x+ 3) (2x+ 4) = 4x ? a) 7xb) 14x c) 6x d) 8x Ans: x Choose the correct option:

5
Fill in with he missing term: (5x + 4)(5x – 7) = 25x = 25x a) 15x b) 55x c) -3x d) -15x Choose the correct option: (-15x) x

6
Fill in with the missing term: (-3a - 7)(-3a – 2) = 9a a) 27a b) 15a c) -27a d) -15a Choose the correct option: 27a

7
(-2a + 8)(-2a – 4) = 4a = 4a Fill in with the missing term: (-8a) a) -8a b) 4a c) 8a d) 16a Choose the correct option: - 8a

8
Fill in with the missing term: (5p + 7q) 2 = 25p q 2 (-2a + 5b) 2 = 4a b 2 = 4a b 2 ( -3f - 8g) 2 = 9f g 2 70pq (-20ab) 48fg ab

9
Find the missing term in the following equation: ? a) 2xyb) -2xy c) 12xyd) -12xy ANS: a) 2xy Choose the correct option:

10
Fill in with the missing term: a) = + + ab b) = + ab (-xy) - xy

11
Fill in with the missing term: = (-pq) pq

12
If 6x – 4y = 3, xy = 2, then : 36x y 2 =

13
If (-15p – 4q) = -3, pq = -1, then : 225p q 2 =

14
If (3a + 5b) = - 4, 9a b 2 = -14, then : ab= (one)

15
If 9m n 2 = -3, mn = 2, then: 3m + 7n =

16
If 25a b 2 = 216, ab = -4, then: 5a – 9b =

17
If 4a b 2 = 48, ab = -2, then: a – 6b =

18
If 25x y 2 = -90, and 5x + 8y =10, then : 5x – 8y =

19
If 256x y 2 = 72, 16x - 9y = 12p and 16x + 9y = 3q, then : pq =

20
If, then :

21
If, then :

22
If, then :

23
If, then :

24
If, then :

25
If, then :

26
Expand : (3a + 2b) 3 = (4x + 7y) 3 = 27a a 2 b + 36ab 2 + 8b x x 2 y+ 588xy y

27
(8y – 5x ) 3 = (3b – 7a) 3 = y y 2 x x x 2 y b b 2 a + 441ba a Expand :

28
(-2d + 7a) 3 = (-a - 6c) 3 = d d 2 a- 294da a 3 - a a 2 c- 108ac c 3 Expand :

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google